Strengthening Collaboration: UiTM Delegates Attend the International Collaboration on Pharmacology and Natural Products (ICPNP) 2024 in Bali, Indonesia / Nurul Alyaa Ibrahim and Mohd Nadzri Mohd Najib - Ibrahim, Nurul Alyaa; Mohd Najib, Mohd Nadzri (Faculty of Pharmacy, 2024)
To strengthen the international collaboration between the countries, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Pulau Pinang, Bertam Campus, accepted the invitation to physically attend and participate in the International Collaboration on Pharmacology and Natural Products (ICPNP) 2024, held on August 19-20, 2024, in Bali, Indonesia. ICPNP 2024, hosted by Universitas Mahasaraswati Denpasar (UNMAS), Bali aimed to provide a platform to share knowledge on advanced pharmacology and the study of natural products and herbal medicine, with a focus on integration into clinical practice. This 2-day event was attended by two lecturers from the Faculty of Pharmacy UiTM Pulau Pinang, Bertam Campus: Dr. Mohd Nadzri Mohd Najib, who represented the faculty’s Dean Professor Dato’ Dr. Abu Bakar Abdul Majeed, and Ms Nurul Alyaa Ibrahim as an invited speaker. This event provided a comprehensive schedule that began with an international seminar titled "Advancement in Pharmacology and Clinical Application of Natural Products" on the first day. Ms. Nurul Alyaa presented at the seminar with the topic "Innovative Research in Herbal Medicine: Bridging Traditional and Clinical Practice," which focused on research approaches to integrate herbal medicine into clinical practice. In addition, there were two other speakers, one from Indonesia presenting physicians' perspectives on the use of herbal medicine in primary care and one from the Philippines with a focus on advanced research in natural product development.